Crime and the transition to teenage parenthood - Carine Øien-Ødegaard; Torbjørn Skardhamar (Statistics Norway, Research Department, 2015)
Age-graded social control theory suggests that parenthood can have a preventive effect on crime among adults, but it is unclear whether and how this applies to teenagers, as teenage parenthood and affiliation with crime can have mutual confounding causes. Using individual-level Norwegian administrative register data on the total population of fifteen to nineteen year olds, we assess the relationship between teenage parenthood and criminal activity. We find that teenage parents have an elevated risk of offending compared to non-parents, but that the transition to parenthood is nevertheless related to a within-individual decline in offending. This decline does not seem to be of permanent nature for girls, but for the boys it appears to stabilize on a lower level than before the transition to teenage fatherhood.
Keywords: D19; K49; 330; teenage parenthood; crime; life course; desistance